THE ANALYSIS OF APPLICATION AND CHARACTERISTICS OF THE TOD FATMAWATI AREA - Taki, Herika Muhamad; Pratiwi, Chintia Ayu; Marasabessy, Marsya Auliasyifa (Universitas Trisakti, 2024)
DKI Jakarta is one of the regions on the island of Java and is the National Capital which is the regional center and is included as a Megapolitan area. As a megapolitan area with a population of more than 10 million people, the mobility of its citizens is also increasing. High mobility has an impact on the emergence of new problems for life. The availability of MRT transportation facilities in Jakarta aims to provide a platform for creating a city environment that is oriented towards humans as its users by emphasizing benefits in aspects of functional quality, visual quality and environmental quality. This Research is using Method is quantitative method. Quantitative Method is a Procedure of the research is producing descriptive data through writen words from people or behaviour can be observed with deductive approach. Collecting Data Method is done by Reference way. Reference way is a description about the relevant literature with the certain topic in which found in scientific books or article of journal. The Fatmawati MRT area is one of the transit areas targeted for development for the Transit Oriented Development (TOD) area for the reason that access to this area is quite easy when there is heavy traffic on weekdays, especially when employees leave work.